(untitled) (Homoeopathy for All, 2025)
The Indian Homoeopathic Drug Manufacturers Forum (IHDMF) continues to uphold its legacy as a powerful voice representing the homeopathic pharmaceutical industry in India. Through its dedicated efforts, the forum has made several impactful contributions in 2024–25, reinforcing its commitment to safe, effective, and quality homeopathic medicines.